The dark side of cross-listing: A new perspective from China - Busaba, Walid Y.; Guo, Lin; Sun, Zhenzhen; Yu, Tong (Journal of Banking & Finance, 2015)
The overwhelming majority of Chinese firms that list their stock both in China and abroad had gone public, and listed, abroad first. We find that when companies listed abroad return to China to issue stock and list, they experience poorer post-issuance stock and operating performance in comparison to purely domestic issuers. Also, they raise more funds relative to their sales, leave less money on the table for investors, and incur lower direct flotation costs. Among returning firms, those which raise higher proceeds relative to sales experience poorer long-run stock performance and lower Tobin’s q post issuance. Our results offer a new perspective on cross-listing, which we term ‘dressing-up-for-premium’. Firms from less-developed markets take advantage of the enhanced visibility and prestige associated with the foreign listing to issue shares domestically at inflated prices and favorable terms, and to raise greater proceeds than they can efficiently use.